The Potential of Swampland Microalgae as Nitrogen Provider - Lestari, Primastya Ayu; Gofar, Nuni; Budianta, Dedik (JOURNAL OF TROPICAL SOILS, 2018)
This study aimed to identify and explore the potential of microalgae from swampland of South Sumatra as nitrogen contributor for rice plants grown on swampland. Determination of sampling points was done by looking at the presence and abundance of microalgae in the sampling locations.Â  The method used in the sampling is purposive sampling method. The samples were grouped into 3, i.e. culture 1 (B1) derived from rice cultivation area, culture 2 (B2) derived from land that was not cultivated with rice, and culture 3 (B3) derived from swamp water samples. The medium used to culture the microlagae was Johnson's medium. The variables measured were the number of microalgae cells and ammonium concentrations on day 1, 4, 8 and 16 of culturing. Three species of Cyanophyceae class from the swampland were identified, i.e. thread algae, Synedra sp. and Melosira sp. Those microalgae may contribute the maximum amount of available nitrogen of 21.41 Ã¬g mL-1 in the form of ammonium to the rice plants on days 10-12. Microalgae in culture 1 can contribute nitrogen for rice plants in the form of ammonium about 16.23% - 48.71% with the cell density of 7.48 cells mL-1.